The Influence of Husbands’ Knowledge, Attitudes, and Support on Wives’ Antenatal Care Visits - Nurfatimah Nurfatimah; Kadar Ramadhan; Lisda Widianti Longgupa; Nur Aziza Labolo (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Antenatal Care (ANC) coverage reflects access to healthcare during pregnancy. Husbands play a crucial role in encouraging ANC attendance through their knowledge, attitude, and support. This study aimed to analyze the relationship between husbands’ knowledge, attitudes, and support and the frequency of their wives’ ANC visits in Wakai Village, Indonesia. Methods: This analytical cross-sectional study included 40 husbands whose wives were pregnant in the second or third trimester or had delivered within the past month. Total sampling was performed. Data on husbands’ sociodemographic characteristics, knowledge, attitudes, and support toward ANC were collected using structured interviewer-administered questionnaires, while the frequency of ANC visits was verified using the Maternal and Child Health Handbook (KIA). Data were analyzed using the chi-square test and multivariable logistic regression using STATA 15.1. Results: Overall, 47.5% of wives had completed four or more ANC visits. Husbands with good knowledge and positive attitudes tended to have wives with more frequent ANC visits; however, these associations were not statistically significant in the multivariate analysis. In contrast, husbands’ support showed a strong and significant association with ANC utilization. Wives whose husbands provided support were 4.9 times more likely to complete at least four ANC visits than those whose husbands did not provide support (AOR = 4.9; 95% CI: 1.0–35.0; p < 0.05). Conclusion: Husbands’ support was the strongest determinant of regular ANC attendance among pregnant women in this rural setting, whereas knowledge and attitudes alone were not consistently associated with visit frequency. Interventions to improve maternal health in similar contexts should prioritize strengthening husbands’ practical support along with educational efforts.